2022
DOI: 10.1186/s13063-022-06221-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of multimodal intervention care on cachexia in patients with advanced cancer compared to conventional management (MIRACLE): an open-label, parallel, randomized, phase 2 trial

Abstract: Background Cancer cachexia (CC) is a multifactorial process characterized by progressive weight loss, muscle mass, and fat tissue wasting, which adversely affects the quality of life and survival of patients with advanced stages of cancer. CC has a complex and multifactorial pathophysiology, and there is no established standard treatment. Therefore, it is often irreversible and a single treatment modality is unlikely to suppress its progression. We are conducting a randomized trial to investiga… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The last focuses on exercise with psychoeducational support. The target sample size for each study is 30, 20, 112, and 130 patients respectively, 39 , 40 , 41 , 42 hence these offer strong potential to progress this field with more robust evidence.…”
Section: Discussionmentioning
confidence: 99%
“…The last focuses on exercise with psychoeducational support. The target sample size for each study is 30, 20, 112, and 130 patients respectively, 39 , 40 , 41 , 42 hence these offer strong potential to progress this field with more robust evidence.…”
Section: Discussionmentioning
confidence: 99%
“…However, cachexia is recognized as a multisystem syndrome affecting multiple organ systems and causing a wide range of clinical effects. Indeed, consensus is growing that the management of cancer cachexia should reflect this, with multimodal treatment, combining targeted anabolic therapies, antiinflammatories, nutritional supplementation, exercise and treatment of secondary factors advocated [1,2,44]. This is reflected in recent clinical practice guidelines, which recognize the complexity of causes contributing to weight loss in cancer patients and prioritize multimodal care [2].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the field of CC treatment are shifting towards multi‐component interventions, based on the principle that one intervention alone is not sufficient to combat CC 3 and that there may be cumulative or synergistic effects between components. NSAIDs have been included in many of these, 17 , 18 , 19 , 20 despite the lack of robust evidence for their efficacy and safety in this population.…”
Section: Discussionmentioning
confidence: 99%
“…While the search strategies and eligibility criteria differed between these reviews, both concluded that, while there was some evidence of beneficial effects, it was not sufficient to recommend the use of NSAIDs for clinical management of CC outside of clinical trials. However, many recent clinical trials of multi‐component CC interventions have included NSAIDs as a core component 17–20 . Thus, an up‐to‐date assessment of the evidence for NSAIDs in the treatment of CC is required.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation